Biodegradable, Water‐Resistant, Anti‐Fizzing, Polyester Nanocellulose Composite Paper Straws (Adv. Sci. 1/2023). Issue 1 (4th January 2023) - Kwak, Hojung; Kim, Hyeri; Park, Seul‐A; Lee, Minkyung; Jang, Min; Park, Sung Bae; Hwang, Sung Yeon; Kim, Hyo Jeong; Jeon, Hyeonyeol; Koo, Jun Mo; Park, Jeyoung; Oh, Dongyeop X.
Abstract : Biodegradable Anti‐Fizzing Water‐Resistant Straws In article number 2205554, Jun Mo Koo, Jeyoung Park, Dongyeop X. Oh, and co‐workers created a marine‐biodegradable paper straw coated with nanocellulose polyester composites. The straws are not only anti‐fizzing when used with soft drinks, but also highly water‐resistant because the good adhesion of nanocellulose to paper gives homogeneous and seamless surface coatings. The sustainable use of straws is the foundation of a huge environmental preservation.